Ultrasound Integration in Undergraduate Medical Education: Comparison of Ultrasound Proficiency Between Trained and Untrained Medical Students. (2nd September 2015) - Dinh, Vi Am; Dukes, William Seth; Prigge, Jennifer; Avila, Michael
Abstract : Objectives: The benefit of formal ultrasound implementation in undergraduate medical education remains unclear. The goal of this study was to evaluate the effectiveness of ultrasound curriculum implementation during year 1 medical student physical examination teaching on the ultrasound proficiency of medical students. Methods: An ultrasound curriculum was formally implemented at our institution in August 2012 and since then has successfully trained 2 classes of medical students (year 1 and year 2). Year 3 and year 4 medical students did not receive any formal ultrasound training, as the curriculum had not yet been implemented during their preclinical years. With the use of a 22‐point ultrasound objective structured clinical examination (US‐OSCE), trained medical students were compared to untrained medical students. The US‐OSCE tested image acquisition and interpretation of the following systems: ocular, neck, vascular, pulmonary, cardiovascular, and abdominal. Emergency medicine (EM) residents formally trained in bedside ultrasound were also tested with the US‐OSCE to provide a reference standard. Results: There were 174 year 1, 25 year 2, and 19 year 3/year 4 medical students and 30 EM residents tested on the US‐OSCE. Ultrasound‐trained medical students were compared to untrained medical students, and overall US‐OSCE scores ± SD were 91.4% ± 14.0% versus 36.1% ± 21.4% ( P < .001), respectively. The EM resident group had an overall score of 99.1% ± 1.8%. The absolute percentage differences were 7.7% between EM resident and ultrasound‐trained medical student scores and 63.0% between EM resident and untrained medical student scores ( P < .001). Conclusions: Implementation of an ultrasound curriculum in undergraduate medical education showed a significant increase in trained versus untrained medical student ultrasound capabilities.